Snapshot of an On-Going Trade in Reptile Wholesaler, Kebumen, Central Java: Preparation, Trading, and Conservation Implications - Nia Kurniawan; Fitra Arya Nugraha; Andri Maulidi; Anggun Sausan Firdaus; Ahmad Muammar Kadafi; Agung Sih Kurnianto (Graduate Program, 2018)
Indonesia is known as one of the highest supplier on animal illegal trading, especially reptile. The objectives of this study are to reveal the preparation proccess of reptiles in the wholesaler and the flow of illegal trade through deep interview and observation in Kebumen Regency, Central Java, Indonesia. The results showed that wholesaler did some specific processes towards reptile. As much as 289 reptiles were observed to be traded in various conditions. Dry season affect the amount of animal sold. Chinese Ratsnake (Ptyas korros) and Reticulated Python (Malayopython reticulatis) became the most traded commodity within reptile trading, and is reported to be exported to other countries. Trafficking of adult reptiles could threaten their wild population, yet the level of exploration and monitoring toward reptile’s wild population are still low.Keywords: Kebumen, reptile, trade, population, wholesaler